Minimally Invasive Alveolar Ridge Preservation Utilizing an In Situ Hardening β-Tricalcium Phosphate Bone Substitute: A Multicenter Case Series. (14th April 2016) - Leventis, Minas D.; Fairbairn, Peter; Kakar, Ashish; Leventis, Angelos D.; Margaritis, Vasileios; Lückerath, Walter; Horowitz, Robert A.; Rao, Bappanadu H.; Lindner, Annette; Nagursky, Heiner
Abstract : Ridge preservation measures, which include the filling of extraction sockets with bone substitutes, have been shown to reduce ridge resorption, while methods that do not require primary soft tissue closure minimize patient morbidity and decrease surgical time and cost. In a case series of 10 patients requiring single extraction, in situ hardening beta-tricalcium phosphate ( β -TCP) granules coated with poly(lactic-co-glycolic acid) (PLGA) were utilized as a grafting material that does not necessitate primary wound closure. After 4 months, clinical observations revealed excellent soft tissue healing without loss of attached gingiva in all cases. At reentry for implant placement, bone core biopsies were obtained and primary implant stability was measured by final seating torque and resonance frequency analysis. Histological and histomorphometrical analysis revealed pronounced bone regeneration (24.4 ± 7.9% new bone) in parallel to the resorption of the grafting material (12.9 ± 7.7% graft material) while high levels of primary implant stability were recorded. Within the limits of this case series, the results suggest that β -TCP coated with polylactide can support new bone formation at postextraction sockets, while the properties of the material improve the handling and produce a stable and porous bone substitute scaffold in situ, facilitating the application of noninvasive surgical techniques.